Methodology of the RAND Health Reform Opinion Study - Carman, Katherine Grace (Rand Health Q, 2015)
The Affordable Care Act has already and will continue to lead to significant changes in health insurance coverage. Understanding insurance transitions is critical to evaluating the success of the reform and to identifying opportunities for improvement. The RAND Health Reform Opinion Study uses the American Life Panel to study transitions in health insurance enrollment from 2013 through 2015. Methodology of the RAND Health Reform Opinion Study provides a description of the methodology the authors use to track health insurance choices between November 2014 and December 2015.